High quality factor, protein-based microlasers from self-assembled microcracks. (14th April 2021) - Nguyen, Tam Trong; Mai, Hanh Hong; Pham, Thin Van; Nguyen, Thau Xuan; Ta, Van Duong
Abstract: In the last decade, microlasers with biological origin have shown their great potential in biosensing and bioimaging. Several micro-structures have been developed for high quality ( Q ) factor biolasers including Fabry–Pérot, distributed feedback and whispering gallery mode cavities. However, the fabrication of these lasers is generally complicated and their operation is strongly affected by cavity defects. In this work, we demonstrate random protein-based microlasers fabricated by a simple one-step self-assembled method. The lasing can be achieved from microcracks with random structures. The lasing threshold is around 14 mJ cm −2 and the quality factor of lasing modes can be up to 3 × 10 3 which are comparable with other conventional biolasers. Our work opens a new possibility for the fabrication of high Q factor microlasers from biocompatible materials, with great potential for biosensing and biomedical applications.